Simple oxalate precursor route for the preparation of barium-strontium titanate: Ba1-xSrxTiO3 powders - Khollam, Y. B.; Deshpande, S. B.; Potdar, H. S.; Bhoraskar, S. V.; Sainkar, S. R.; Date, Sadgopal K. (Materials Characterization, 2005)
A simple one-step cation-exchange reaction between the stoichiometric solutions of ammonium titanyl oxalate (ATO) and barium hydroxide+strontium nitrate at room temperature (RT) is investigated successfully for the quantitative precipitation of barium-strontium titanyl oxalate (BSTO): Ba1-xSrxTiO(C2O4)(2).4H(2)O (x=0.25) precursor powders with nearly theoretical yield (greater than or equal to99%). The pyrolysis of BSTO at 730degreesC/4 h in air produced barium-strontium titanate (Ba1-xSrxTiO3; BST) powders. The characterization studies on BSTO and BST powders by using various physico-chemical techniques: micro- and chemical analysis, differential thermal analysis (DTA)/thermo-gavimetric analysis (TGA), XRD, FTIR, X-ray fluorescence (XRF) and scanning electron microscopy (SEM) revealed that the powders formed are cubic, highly pure, stoichiometric and sub-micron-sized with nearly uniform size and shape distribution. The ceramic compacts obtained by sintering the BST pellets at 1300degreesC/4 It showed density similar to95%, dielectric constant epsilon(Tc)similar to9500, tan delta-0.15% and T(C)similar to32 degreesC. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: barium-strontium titanate; barium-strontium titanyl oxalate; permittivity; XRF